The innocent man : murder and injustice in a small town - Grisham, John. (New York : Dell, 2007)
Presents a comprehensive study of the controversial murder trial involving baseball player Ron Williamson.
New York Times, December 2006
Adult
Adult
New York Times
Keywords: Williamson, Ronald Keith, -- 1953-2004 -- Trials, litigation, etc; Trials (Murder) -- Oklahoma; Judicial error -- Oklahoma; Capital punishment -- Oklahoma; Williamson, Ronald Keith, -- 1953-2004.; Trials (Homicide) -- Oklahoma; Administration of criminal justice -- Oklahoma; Capital punishment -- Oklahoma